Transition risk analysis in the mining sector and its implications for environmental conflict: A Case study approach - Pepy Hapita Sari (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Climate change has become a major challenge of the 21st century, driving a global transition toward low-carbon energy to reduce greenhouse gas emissions, with a target of Net Zero Emissions (NZE) by 2050. The mining sector, particularly coal, faces significant transition risks, such as declining coal demand, rising operational costs, and social and environmental impacts due to increasingly stringent emission reduction policies. PT ABC, as a major coal producer in Indonesia, must adapt by shifting to renewable energy, reducing its dependence on coal, and managing transition risks while seizing opportunities for energy diversification. Methods: This study analyzes the transition risks faced by PT ABC, focusing on the impact of global climate policies, fluctuations in international carbon prices, and the shift toward renewable energy on the company’s financial performance. Findings: The analysis shows that the company needs to reduce emissions by approximately 993,478 tons of CO₂eq per year to meet Indonesia’s emission reduction targets in the Enhanced Nationally Determined Contributions (ENDC), with an additional annual cost of around IDR 29.8 billion at a carbon price of IDR 30,000 per ton. If carbon prices increase, costs could reach IDR 140.5 billion or IDR 198.7 billion by 2030. This study identifies four main transition risks: government policy changes, carbon price fluctuations, declining coal demand, and the implementation of a carbon tax. Conclusion: To mitigate financial and operational impacts, PT ABC needs to adopt environmentally friendly technologies, diversify investments in renewable energy, and improve energy efficiency. These risk mitigation efforts are expected to reduce negative impacts and support the company’s operational sustainability amid the global energy transition. Novelty/Originality of this article: By quantifying emission reduction costs and potential carbon price impacts, it offers insights into strategic measures for coal companies adapting to the low-carbon transition.